The potential of local orange peel-derived eco-enzymes in producing indole acetic acid - Siska Alicia Farma; Nurfa Dewiza Luzik; Salma Sakina; Irma Leilani Eka Putri; Linda Advinda; Azwir Anhar (Acta Biochimica Indonesiana, 2023)
Background: Ecoenzymes, created from the fermentation of organic citrus waste, offer a sustainable method to produce Indole Acetic Acid (IAA), a phytohormone vital for plant growth. This study investigates the potential of these ecoenzymes in promoting sustainable agriculture. Objective: This study aims to evaluate the capacity of ecoenzymes derived from local citrus organic waste to synthesize IAA hormones. Methods: The ecoenzyme was extracted from fruit powders and centrifuged to separate the supernatant. One ml of ecoenzyme supernatant was then mixed with 2 ml of Salkowski reagent and incubated for 12 hours at room temperature in the dark to facilitate reaction. The presence and concentration of IAA were determined using spectrophotometry at a wavelength of 530 nm, while total protein levels were measured using the Warburg-Christian method. Results: ecoenzymes from local citrus sources contain IAA, with the highest concentration observed in sample 7A (30.26 µg/ml). The ecoenzyme exhibited favorable characteristics, including an average degree of acidity of 3.55, and the highest total protein content was found in sample 2A (144.277 mg/mL). Conclusion: Ecoenzymes from local orange peels successfully produce IAA, supported by fermentation-induced microbial activity and acidic conditions. This highlights their potential in sustainable agriculture.